The impacts of the COVID-19 crisis on maternal and child malnutrition in Myanmar: What to expect, and how to protect - Headey, Derek D.; Cho, Ame; Goudet, Sophie; Oketch, Jecinter Akinyi; Oo, Than Zaw (International Food Policy Research Institute, 2020)
The COVID-19 crisis in Myanmar poses a very serious risk to the nutritional status of vulnerable populations, notably women and children, as well as poor urban populations and internally displaced persons. The COVID-19 crisis will hit vulnerable groups through multiple mechanisms.